Understanding and treating incels case studies, guidance, and treatment of violence risk in the involuntary celibate community - Van Brunt, Brian; Taylor, Chris 1967- (Routledge, Taylor & Francis Group, 2021)
"Understanding and Treating Incels is an indispensable guide for professionals who want to better understand the involuntary celibate movement, assess individuals' potential for violence, and offer treatment approaches and prevention efforts."